2012
DOI: 10.14411/eje.2012.022
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia infection in Trissolcus species (Hymenoptera: Scelionidae)

Abstract: Abstract. Wolbachia is a maternally transmitted intracellular symbiont which causes reproductive distortions in the arthropods it infects. In recent years there has been an increasing interest in using Wolbachia as a potential tool for biological control by genetic manipulation of insect pests. In the present paper we report Wolbachia infection in several Trissolcus wasps (Hymenoptera: Scelionidae) which are important egg parasitoids of the sunn pest, Eurygaster integriceps Puton (Heteroptera: Scutellaridae). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The present study was performed to investigate the presence or absence of reproductive associated endosymbiotic bacteria in sand flies in Turkey. Molecular studies in Turkey have previously reported that Wolbachia infection was detected in Trissolcus species, Culex pipiens and Phlebotomus spp 32 34 . Further studies are needed to determine the extent and the potential biological significance of Wolbachia spp .…”
Section: Discussionmentioning
confidence: 99%
“…The present study was performed to investigate the presence or absence of reproductive associated endosymbiotic bacteria in sand flies in Turkey. Molecular studies in Turkey have previously reported that Wolbachia infection was detected in Trissolcus species, Culex pipiens and Phlebotomus spp 32 34 . Further studies are needed to determine the extent and the potential biological significance of Wolbachia spp .…”
Section: Discussionmentioning
confidence: 99%
“…Several host‐shift events among closely related species, as inferred from patterns of Wolbachia strain distributions on host phylogenies, support the PDE hypothesis, e.g. in weevils (Lachowska, Kajtoch, & Knutelski, 2010; Sanaei et al ., 2019), Trissolcus wasps (Guz et al ., 2012), and Drosophila (Haine, Pickup, & Cook, 2005; Turelli et al ., 2018). By contrast, in some case studies focused on certain arthropod families or genera, only a negligible part of the data, if any, appeared to indicate a PDE, e.g.…”
Section: Factors Influencing Host Shiftsmentioning
confidence: 99%
“…The mean phylogenetic difference between Pip group and other isolates under the Super group A was also found higher (25.0%). In addition a high genetic diversity (23.1%) was also determined among the WolKys1 isolate and Wolbachia isolates reported from Trissolcus rufiventris, T. flavipes and T. grandis in Turkey which are known to be specific enemies of stink bugs (17).…”
Section: Methodsmentioning
confidence: 90%